Nature-based mind–body intervention for test anxiety in adolescents: a feasibility study - Xuan Zeng; Xuan Zeng; Yarui Zhang; Yarui Zhang; Yarui Zhang; Ziyan Chu; Tianyong Chen; Tianyong Chen (Frontiers in Psychology)
IntroductionTraditional interventions for test anxiety often fall short of addressing the specific needs of adolescents and educational institutions due to issues of stigmatization and professionalization. In contrast, nature-based interventions (NBIs) have gained traction for their potential to enhance mental health, as they are generally accepted and cost-effective, thereby offering a promising alternative for alleviating test anxiety.MethodsThis study seeks to investigate the feasibility of a nature-based mind– body intervention (NMI) designed to reduce test anxiety among adolescents by integrating elements of NBIs and mind–body therapies (MBTs).ResultsThe findings suggest that NMI can significantly diminish excessive test anxiety and academic stress, along with alleviating symptoms of general anxiety and depression.DiscussionThis approach presents a low-stigma, low-cost strategy for managing test anxiety in adolescents and offers valuable insights for mental health policymakers. Furthermore, it may enhance academic performance and broaden educational access for disadvantaged populations in developing countries.